Optimal Long-Term Financial Contracting - DeMarzo, Peter M.; Fishman, Michael J. (Review of Financial Studies, 2007)
We develop an agency model of financial contracting. We derive long-term debt, a line of credit, and equity as optimal securities, capturing the debt coupon and maturity; the interest rate and limits on the credit line; inside versus outside equity; dividend policy; and capital structure dynamics. The optimal debt-equity ratio is history dependent, but debt and credit line terms are independent of the amount financed and, in some cases, the severity of the agency problem. In our model, the agent can divert cash flows; we also consider settings in which the agent undertakes hidden effort, or can control cash flow risk.